2021
DOI: 10.1089/ten.tea.2020.0061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bilayer Silk Fibroin Grafts for Tubular Esophagoplasty in a Porcine Defect Model

Abstract: Surgical reconstruction of tubular esophageal defects with autologous gastrointestinal segments is the gold standard treatment to replace damaged or diseased esophageal tissues. Unfortunately, this approach is associated with adverse complications including dysphagia, donor site morbidity and in some cases patient death. Bi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Indeed, BLSF grafts were capable of promoting multi-layered, urothelial formation in neotissues with prominent UP3A and pan-CK protein expression. This pattern of constructive remodeling is similar to our previous observations using BLSF scaffolds for bladder and esophageal tissue repair (Affas et al, 2019;Gundogdu et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, BLSF grafts were capable of promoting multi-layered, urothelial formation in neotissues with prominent UP3A and pan-CK protein expression. This pattern of constructive remodeling is similar to our previous observations using BLSF scaffolds for bladder and esophageal tissue repair (Affas et al, 2019;Gundogdu et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…However, histological and IHC evaluations confirmed that central neotissue areas supported by BLSF grafts were immature at sacrifice relative to peripheral neotissues and NSC suggesting longer periods of stenting may be necessary for complete regeneration and stricture prevention. Indeed, the duration of stent deployment has been shown to play a major role in determining the risk of stricture occurrence in reconstructed visceral hollow organs (Takimoto et al, 1994;Gundogdu et al, 2021). In addition, the in vivo degradation profile of BLSF matrices was also found to be insufficient for maintaining upper urinary tract function following stent removal.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the deployment of caspase inhibitors to encourage www.nature.com/scientificreports/ esophageal tissue regeneration may be a promising therapeutic approach in cases wherein epithelial formation is impeded following surgical reconstruction. Preclinical investigations of acellular biomaterials for reconstruction of long-gap, tubular esophageal defects often show deficiencies in the ability of tissue engineered grafts to support skeletal muscle formation as well as de novo vascularization and innervation of neotissues 44,45 . A better understanding of signal transduction pathways which govern myogenesis, neurogenesis, and vascularization during healing of patch defects as described in the current study may inform the development of instructive biomaterial designs which can improve tubular neotissue maturation via controlled release of selective pathway agonists.…”
Section: Discussionmentioning
confidence: 99%
“…The multi-step method is based on the perspective of esophageal structure bionics, combining different layers of scaffold materials through a certain link method. Joshua et al prepared the silk fibroin double-layer scaffold by solution pouring ( Gundogdu et al, 2021 ). Rossella et al used electrospinning and temperature-induced sedimentation to construct two double-layer scaffolds ( Pisani et al, 2020 ).…”
Section: Multi-layer Esophageal Scaffoldsmentioning
confidence: 99%
“…If the adhesion between scaffolds is poor, the multi-layer scaffolds will fall off or shift, which will seriously affect the repair effect of the esophagus. The connection modes between the layers of multi-layer scaffolds include the solution casting method ( Gundogdu et al, 2021 ), temperature-induced precipitation method ( Dorati et al, 2017 ), solvent volatilization method of electrospinning ( Chung et al, 2015 ), and glue bonding ( Deng et al, 2019 ). The first three methods are not universally applicable because solutions or solvents may dissolve the active components such as protein, growth factor in the scaffold, and too high or low temperature is not conducive to the introduction of proteins and cells into the scaffold.…”
Section: Problems and Challengesmentioning
confidence: 99%